Profitability in Moderating the Effects of Business Risk, Company Growth and Company Size on Debt Policy - Anisa Nurfitriana; Fachrurrozie Fachrurrozie (Journal of Accounting and Strategic Finance, 2018)
The purpose of this research is to analyze the influence of business risk, corporate growth, and firm size on debt policy with profitability as moderating in manufacturing subsector industries of consumption goods listed in Indonesia Stock Exchange (IDX) in 2012-2016. The population of the research was manufacturing subsector industries of consumption goods listed in Indonesia Stock Exchange (IDX) in 2012-2016. The sample was 21 manufacturing subsector industries of consumption goods with some characteristics of sample selection using purposive sampling method. Hypothesis analysis method used in this research is a Moderated Regression Analysis (MRA). The result of the study showed that business risk, corporate growth, and firm size did not influence debt policy. Profitability can strengthen business risk to debt policy. Profitability can strengthen corporate growth to debt policy. Profitability fails to moderate firm size to debt policy. The conclusion of the research is two of six hypotheses accepted, and these are Profitability can weaken business risk to debt policy. Profitability can strengthen corporate growth to debt policy.